Button Battery Intake as Foreign Body in Chinese Children: Review of Case Reports and the Literature. Issue 6 (June 2015) - Liao, Wenjing; Wen, Guangyi; Zhang, Xiaowen
Abstract : Objectives: Button batteries have been recognized as one of the dangerous foreign bodies to children for more than 30 years, but few related studies have been published to give more concern in China. Methods: We reported 6 cases of button battery intake as foreign body in children. The Chinese literature on button battery as foreign body in children was reviewed. Results: The interval between the accidental ingestion and battery removal ranged from 6 hours to 3 days. Two patients had no sequela, 3 patients had tracheoesophageal fistulas, and 1 patient had nasal septal perforation. Twenty-eight articles about button battery as foreign body in children were obtained by Chinese-language literature searches including 25 case reports, 2 health education articles, and 1 imaging article. In total, 172 cases of button battery intake as foreign body in children were identified, 23 and 10 of the 159 cases involving nasal button battery lodgment developed nasal septal perforation and nasal adhesion, respectively. Tracheoesophageal fistula was identified in 4 of the 12 ingestion cases. One case of button battery intake was in external auditory canal. Conclusions: A small number of children with button battery as foreign body were reported in China, which is 1 of the biggest countries with large population of children.